THE APPLICATION OF MUSHARAKAH MUTANAQISAH IN PROPERTY FINANCING: EXPERIENCE OF AFFIN ISLAMIC BANK BERHAD - Ali, Mohammad Mahbubi; Abd Rahman, Ahmad Husni; Rahim , Mohd Faiz (Jurnal Syariah, 2023)
The widespread adoption of the tawarruq contract by Islamic banks in their deposit and financing offerings has spurred the emergence of mushārakah mutanāqisah as an alternative for Islamic property financing. Affin Islamic Bank Berhad is among the Islamic banks that offer mushārakah mutanāqisah as the core Shari‘ah contract in their Islamic property financing services. This type of financing is offered to customers for completed properties and those that are under construction. In the context of Islamic property financing, mushārakah mutanāqisah refers to a structure where the customer assumes the role of the registered property owner while the bank holds ownership shares in the form of beneficial ownership. Bank Negara Malaysia (BNM) has released multiple Policy Documents regarding Shari‘ah contracts as guidelines to ensure uniformity in the application of Shari‘ah contracts across Islamic financial products and services. Islamic banks are required to adhere to these guidelines, including the mushārakah mutanāqisah. Thus, this paper intends to study the application of mushārakah mutanāqisah in property financing based on Affin Islamic Bank’s experience in adopting the related Policy Documents issued by BNM. The findings from this paper would shed light and provide valuable insights into implementing the related guidelines to mushārakah mutanāqisah and its impact on the Islamic finance industry in Malaysia. Document analysis approach was used to analyse library data gathered from previous studies and relevant policy documents.